A method for optimizing stencil cleaning time in solder paste printing process. Issue 4 (2nd September 2019) - Yu, JiangYou; Cao, Le; Fu, Hao; Guo, Jun
Abstract : Purpose: Stencil cleaning is an important operation in solder paste printing process. Frequent cleaning may interrupt printing process and increase idle time, as well as loss for performing cleaning. This paper aims to propose a method to optimize the stencil cleaning time and reduce unnecessary cleaning operations and losses. Design/methodology/approach: This paper uses a discrete-time, discrete-state homogeneous Markov chain to model the stencil printing performance degradation process, and the quality loss during the stencil printing process is estimated based on this degradation model. A stencil cleaning decision model based on renewal reward theorem is established, and the optimal cleaning time is obtained through a balance between quality loss and the loss on idle time. Findings: A stencil cleaning decision model for solder paste printing is established, and numerical simulation results show that there exists an optimal stencil cleaning time which minimizes the long-term loss. Originality/value: Stencil cleaning control is very important for solder paste printing. However, there are very few studies focusing on stencil cleaning control. This research contributes to developing a model to optimize the stencil cleaning time in solder paste printing process.